The economics of child well-being - Gabriella Conti; James J. Heckman (Institute for the Study of Labor (IZA), 2012)
This chapter presents an integrated economic approach that organizes and interprets the evidence on child development. It also discusses the indicators of child well-being that are used in international comparisons. Recent evidence on child development is summarized, and policies to promote child well-being are discussed. The chapter concludes with some open questions and suggestions for future research.
Keywords: J13; I21; D03; D04; 330; child development; human capital; early childhood education; Kinder; Sozialer Indikator; Frühkindliche Bildung